The Economics of Constitutional Monarchy: The Antipodean Anachronism? - Simpson, John (Centre for Research in Applied Economics, Curtin Business School, 2010)
The United Kingdom, since the end of the Second World War, has not been vitally trade or defence dependent on Australia. Australia since the advent of European Economic Community has not been vitally trade dependent on the United Kingdom. There are continuing trade and investment relationships but, any strong economic, financial and political connections have long since evaporated. Yet, the Union Jack remains at the corner of the Australian flag. A British constitutional monarchy persists. Australia is a wealthy, independent and rapidly growing developed country, with its own identity, destiny and pride of place in the world. The United Kingdom and Australia of course remain friendly allies. This paper does not deal with past British cultural connections. It merely demonstrates econometrically that linkages of an economic, financial and political nature are not sufficiently strong enough to perpetuate a constitutional monarchy for Australia. A three country model is presented, to include the only other developed Southern Hemisphere British constitutional monarchy (that of New Zealand), for purposes of comparison.